New indane and naphthalene derivatives from the rhizomes of Kniphofia reflexa Hutchinson ex Codd. (August 2018) - Sema, Denis Kehdinga; Meli Lannang, Alain; Tatsimo, Simplice J.N.; Mujeeb-ur-Rehman,; Yousuf, Sammer; Zoufou, Denis; Iqbal, Urooj; Wansi, Jean Duplex; Sewald, Norbert; Choudhary, M. Iqbal
Graphical abstract: Highlights: New indane and naphthalene derivatives from the rhizomes of Kniphofia reflexa Hutchinson ex Codd. Their chemical structures were elucidated using 1D and 2D NMR spectroscopic methods and by X-ray crystallography. Compound 3 was found to be highly cytotoxic, while compounds 1, and 10 showed moderate cytotoxic. Abstract: Two new (1 -2 ) and eight known (3 -10 ) secondary metabolites were isolated from the rhizomes of Kniphofia reflexa Hutchinson ex Codd. Among them, an indane derivative kniphofiarindane (1 ), and naphthalene derivative kniphofiarexine (2 ), were identified as new natural products. 1D- and 2D-NMR spectroscopic studies together with single-crystal X-ray diffraction techniques were employed in the structural elucidation of the new compounds, 1 and 2 . These compounds were evaluated for their cytotoxic effect against kidney epithelial cell line (LLC-MK2). Compound 3 was found to be highly cytotoxic, while compounds 1, and 10 showed moderate cytotoxicity with CC50 values of 4.44 ± 0.79, 16.35 ± 1.54, and 11.24 ± 1.22 μg/mL, respectively against the tested standard Gleevec (Imatinib), (CC50  = 18.50 ± 1.21 μg/mL). Compounds 8, and 9 also showed moderate anti-inflammatory activity (CC50  = 38.7 ± 4.90, and 20.00 ± 4.40 μg/mL, respectively) against ROS production.